Mutations in the putative calcium-binding domain of polyomavirus VP1 affect capsid assembly. - Haynes, J I (1993)
Calcium ions appear to play a major role in maintaining the structural integrity of the polyomavirus and are likely involved in the processes of viral uncoating and assembly. Previous studies demonstrated that a VP1 fragment extending from Pro-232 to Asp-364 has calcium-binding capabilities. This fragment contains an amino acid stretch from Asp-266 to Glu-277 which is quite similar in sequence to the amino acids that make up the calcium-binding EF hand structures found in many proteins. To assess the contribution of this domain to polyomavirus structural integrity, the effects of mutations in this region were examined by transfecting mutated viral DNA into susceptible cells. Immunofluorescence studies indicated that although viral protein synthesis occurred normally, infective viral progeny were not produced in cells transfected with polyomavirus genomes encoding either a VP1 molecule lacking amino acids Thr-262 through Gly-276 or a VP1 molecule containing a mutation of Asp-266 to Ala. VP1 molecules containing the deletion mutation were unable to bind 45Ca in an in vitro assay. Upon expression in Escherichia coli and purification by immunoaffinity chromatography, wild-type VP1 was isolated as pentameric, capsomere-like structures which could be induced to form capsid-like structures upon addition of CaCl2, consistent with previous studies. However, although VP1 containing the point mutation was isolated as pentamers which were indistinguishable from wild-type VP1 pentamers, addition of CaCl2 did not result in their assembly into capsid-like structures. Immunogold labeling and electron microscopy studies of transfected mammalian cells provided in vivo evidence that a mutation in this region affects the process of viral assembly.